IDENTIFICATION OF PTERIDOPHYTES DIVERSITY IN THE MOUNTAINOUS AREA OF BUNTU SARONG VILLAGE, MASALLE DISTRICT, ENREKANG REGENCY - Hasmiati, Hasmiati; Rukmana, Musma; Agustina, Tika Putri; Watung, Fernando Andre (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2024)
Ferns (Pteridophyte) are members of the kingdom plantae that contribute to Indonesia's biodiversity, especially the diversity of flora. Ferns have an important role in maintaining the balance of the ecosystem. In addition to having ecological value in the ecosystem as a source of germplasm, ferns also have the potential to be useful to support people's lives. However, in fact ferns are still less well-known and receive less attention than other plants. This is because one of the reasons is that people are less familiar with ferns. This study aims to identify the types of ferns (Pteridophyte) in the mountainous area of ​​Buntu Sarong Village, Masalle District, Enrekang Regency. Data collection was carried out using the exploration method at certain points in the research location that were considered potential, then recording, documenting, identifying and classifying the Pterydophyta found. The research at the research location successfully identified and documented 16 species of Pteridophyte, namely Psilotum nudum, Lycopodium, Selaginella delicatula, Equisetum hyemale, Odontosoria chinensis, Gleichenia linearis, Adiantum sp., Christella parasitica, Aspelinum nidus, Cyathea cooperi, Angiopteris evecta, Deparia petersenii, Microsorum punctatum, Drynaria quercifolia, Microsorum punctatum, Microsorum scolopendria, Drymoglossum piloselloides. The identified Pteridophyte are classified into 13 families (Lycopodiaceae, Psilotaceae, Equisetaceae, Marattiaceae, Lindsaceae, Gleicheniaceae, Adiantaceae, Thelypteridaceae, Asplenidaceae, Chyatheaceae, Athyriaceae, Polypodiaceae) and 5 classes (Lycopodiopsida, Psilotopsida, Equisetopsida, Marattiopsida, Polypodiopsida).